2016
DOI: 10.1596/1813-9450-7624
|View full text |Cite
|
Sign up to set email alerts
|

School Grants and Education Quality: Experimental Evidence from Senegal

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…According to (Becker, 1964), human capital is directly needed in the production process, more explicitly human capital increases the productivity of employees in all tasks, but normally differently in different tasks and different organizations, e. which although generalized makes sense since the level of knowledge and ability of employees is directly related to the function of productivity. When it comes to grants in education according to Carneiro et al (2020) sometimes government and authorities does not know the needs of the schools and universities and therefore we do not see improvement in their general scores .whilst when comes to the labor market to select and retain a satisfying employee there are some issues that needs to be developed as training and development and interaction of organizations strategy with human resources development , in order to reach competitive advantage in the field that they are working Holland et al (2007). Sun, M., Penner, E. K., & Loeb, S. ( 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Becker, 1964), human capital is directly needed in the production process, more explicitly human capital increases the productivity of employees in all tasks, but normally differently in different tasks and different organizations, e. which although generalized makes sense since the level of knowledge and ability of employees is directly related to the function of productivity. When it comes to grants in education according to Carneiro et al (2020) sometimes government and authorities does not know the needs of the schools and universities and therefore we do not see improvement in their general scores .whilst when comes to the labor market to select and retain a satisfying employee there are some issues that needs to be developed as training and development and interaction of organizations strategy with human resources development , in order to reach competitive advantage in the field that they are working Holland et al (2007). Sun, M., Penner, E. K., & Loeb, S. ( 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Participating in the Erasmus + program and its external dimension by supporting the modernization of higher education is in first steps in increasing the quality of higher education. Carneiro et al (2020) found that impact of grants in education in quality and learning has its impact when its combined with government and heads of school's involvement 'especially on girls and students with high ability levels at baseline, at a cost effectiveness rate commensurate with other interventions that aim to improve education outcomes in low-income countries'. In Kosovo population is the youngest in Europe and unemployment levels are approximately as high as 35 percent.…”
Section: Eu Investments In the Education Sector In Kosovo 2008-2015mentioning
confidence: 99%
“…Resultado más positivo entre la relación de los recursos humanos de la escuela con los resultados educativos es el encontrado en Senegal (Carneiro et al, 2016), donde un ECA mira un programa de becas diseñado para mejorar la elección de becarios y su efecto en los resultados en aprendizaje. El efecto encontrado es positivo y duradero (al menos dos años).…”
Section: Ensayos De Control Aleatoriounclassified